2007
DOI: 10.1097/jcp.0b013e3180a76dc0
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between HTR2C Gene Polymorphisms and the Metabolic Syndrome in Patients With Schizophrenia

Abstract: The use of antipsychotics is associated with metabolic side effects, which put patients with schizophrenia or related disorders at risk for cardiovascular morbidity. The high interindividual variability in antipsychotic-induced metabolic abnormalities suggests that genetic makeup is a possible determinant. In this cross-sectional study, we investigated whether genotypes of the HTR2C receptor are associated with the metabolic syndrome in patients using antipsychotics. Patients were identified from a schizophren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
2
3

Year Published

2009
2009
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 34 publications
4
62
2
3
Order By: Relevance
“…In 2007, Mulder et al first demonstrated that genetic variants in 5-hydroxytryptamine (serotonin) receptor 2C is associated with MetS in patients with schizophrenia. 11 They replicated the finding in a recent report and further demonstrated that, the increased risk for MetS, is particularly strong in carriers of the 5-hydroxytryptamine (serotonin) receptor 2C rs1414334 C allele using clozapine or risperidone. 12 Another study investigated association between methylenetetrahydrofolate reductase genetic variants and MetS in schizophrenic patients receiving AAPs and demonstrated that the methylenetetrahydrofolate reductase 677T allele is associated with a 3.6-fold greater risk for developing AAP-associated MetS and the 677TT genotype may place individuals at greater risk for insulin resistance with greater central adiposity.…”
Section: Introductionsupporting
confidence: 74%
“…In 2007, Mulder et al first demonstrated that genetic variants in 5-hydroxytryptamine (serotonin) receptor 2C is associated with MetS in patients with schizophrenia. 11 They replicated the finding in a recent report and further demonstrated that, the increased risk for MetS, is particularly strong in carriers of the 5-hydroxytryptamine (serotonin) receptor 2C rs1414334 C allele using clozapine or risperidone. 12 Another study investigated association between methylenetetrahydrofolate reductase genetic variants and MetS in schizophrenic patients receiving AAPs and demonstrated that the methylenetetrahydrofolate reductase 677T allele is associated with a 3.6-fold greater risk for developing AAP-associated MetS and the 677TT genotype may place individuals at greater risk for insulin resistance with greater central adiposity.…”
Section: Introductionsupporting
confidence: 74%
“…In our previous two studies, we used a slightly different set of criteria to diagnose the metabolic syndrome. 8,9 In those two studies, the metabolic syndrome was diagnosed when three or more of the following four metabolic criteria were met: waist circumference 4102 cm (male) or 488 cm (female), triglycerides X1.7 mmol l À1 , HDL cholesterol o1.0 mmol l…”
Section: Discussionmentioning
confidence: 99%
“…However, in western and northern Europeans, allele G appears to be the major allele, which is confirmed in our earlier research. 8,9 In the analysis we therefore considered the C-allele as the variant allele. For the Asians and Africans in our study, the variant rs1414334 allele would actually be the G-allele.…”
Section: Determinantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gene coding for the 5-HT2c receptor is an example of a drug targeting receptor with a relatively unknown phenotype. One of the suggested clinical phenotypes of the HTR2C gene is a function in regulation of food intake and weight gain but results are conflicting [18][19][20][21][22][23][24][25]. This pharmacodynamic polymorphism is one example of many others.…”
Section: Resultsmentioning
confidence: 99%